TERT aberrancies: a screening tool for malignancy in follicular thyroid tumours. Issue 7 (July 2018) - Paulsson, Johan O; Mu, Ninni; Shabo, Ivan; Wang, Na; Zedenius, Jan; Larsson, Catharina; Juhlin, C Christofer
Abstract : Telomerase reverse transcriptase ( TERT ) promoter mutations have been linked to adverse clinical parameters in thyroid cancer, but TERT -expressing tumours are not always mutated. Little is known regarding other TERT -related genetic aberrations. To delineate the role of TERT gene aberrancies in follicular thyroid tumours, 95 follicular carcinomas (FTCs), 43 follicular adenomas (FTAs) and 33 follicular tumours of uncertain malignant potential (FT-UMPs) were collected. The tumours were assayed for TERT expression, TERT promoter mutations, TERT promoter hypermethylation and TERT gene copy number (CN) alterations and the results were compared to clinical parameters. Cases with mutation, detectable mRNA expression, CN gain or hypermethylation were classified as TERT aberrant, and these aberrancies were regularly found in FTC and FT-UMP but uncommonly found in FTA. In total, 59% FTCs and 63% FT-UMPs exhibited one or more of these TERT gene aberrancies. Moreover, 24 out of 28 FTCs (86%) with TERT expression displayed an evident TERT gene aberration, and statistics showed an increased risk for relapse in FTCs with TERT expression, CN gain or hypermethylation. We conclude that TERT expression in follicular thyroid tumours is coupled to promoter mutations, CN gain and increased promoter methylation. The molecular similarities regarding TERT aberrations between the FTC and FT-UMP groups indicate that a significant subset of FT-UMP cases may display future recurrences. TERT aberrancies are thus promising as future additional markers for determining malignant potential of follicular thyroid tumours.